Behaviour and Inspection of Novel Non-Crimp Dry Thick Reinforcement Fabrics - BU JLDAIN, HAFETH (Université d'Ottawa / University of Ottawa, 2015)
Aerospace structural components made from polymer matrix composites (PMCs) offer numerous advantages. Their high stiffness and high strength combined with low densities enable lower fuel consumption coupled with higher payloads. As a result, PMCs provide an important economic advantage over typical metallic airframes. Textile reinforcements for PMCs are made by assembling reinforcement fibres, typically carbon. Then, the textile reinforcements are typically cut into smaller pieces, stacked, draped and assembled into a dry assembly called a preform, the shape of which generally approaches that of the PMC part to be made. This manufacturing process is labour intensive and expensive. Novel thick, net-shape, drapable, high vf textile reinforcements used toward manufacturing aerospace PMCs are being developed at the University of Ottawa. The technology enables the manufacturing of flat, drapable multilayered near net-shape preforms. The bending and in-plane shear behaviours of such novel thick reinforcement textiles was investigated to understand and define the behaviour of such thick fabric reinforcements when formed into required shapes. A bending apparatus was developed for investigating the bending behaviour of these novel thick reinforcement fabrics and an articulated frame shear rig was used for investigating the in-plane shear behaviour. A non-destructive inspection method using infrared imaging was used for investigating and identifying flaws and defects in these thick, dry textile reinforcements, aiming at increasing the quality and reproducibility of the final PMC parts made from these reinforcements.
Keywords: Thick reinforcement textile; Non-crimp fabric; Infrared thermography; NDT method; Bending behaviour; In-plane shear behaviour; Textile inspection